Factors influencing employment rates and states after liver transplantation in China: A multi‐centre cross‐sectional study - Dan Zhang; Jing Wang; Zijun Tao; Ying Shi; Huili Wang; Tiantian Chang; Xiaoyu Jiang; Xiaofei Li (Wiley, 2023)
Abstract Aim The aim of this study was to assess employment rates and states and the factors influencing liver transplant recipients in China. Design A cross‐sectional study. Methods A total of 212 liver transplant recipients were included in this study. Questionnaires for general situation information and the Hospital Anxiety and Depression Scale, Perceived Social Support Scale and Chronic Disease Self‐Efficacy Scale were used. Results Among the liver transplantation, 212 recipients were included in the study, 125 (59%) were employed after liver transplantation compared with 148 (69.8%) who were employed before liver transplantation. Among the 125 recipients that returned to work, only 38.2% thought their employment states were good before liver transplantation, while 81.6% thought that their employment states were good after liver transplantation. Gender, age and employment status before transplantation, aetiology of liver disease, number of physical activities, per capita monthly income, comorbidity and depression were significantly associated with return to work. Self‐efficacy, social support, liver function and nature of work were significantly associated with employment state.